Suhrawardi’s Modal Syllogisms - موحد ضیاء (جاویدان خرد, 2022)
Suhrawardi’s logic of the Hikmat al-Ishraq is basically modal. So to understand his modal logic one first has to know the non-modal part upon which his modal logic is built. In my previous paper ‘Suhrawardi on Syllogisms’(3) I discussed the former in detail. The present paper is an exposition of his treatment of modal syllogisms. On the basis of some reasonable existential presuppositions and a number of controversial metaphysical theses, and also by confining his theory to alethic modality, Suhrawardi makes his modal syllogism simple in a way that is without precedent